Physiological maturity of pigeonpea at three sowing periods. - Vieira, Roberval Daiton; Nielsen, Ney; Carvalho, Nelson Moreira de; Malheiros, Euclides Braga (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was conducted during the crop season 1985/86 at the experimental area of the Departamento de Fitotecnia da Faculdade de Ciências Agrárias e Veterinárias of the Universidade do Estado de São Paulo (UNESP), Campos of Jaboticabal, SP, Brazil, to study the physiological maturation of pigeonpea (Cajanus cajan (L.) Millsp.) at three sowing periods. Seeding was done at the months of December 1985, January and February 1986 for the first, second and third periods, respectively. Pods were collected weekly, from previously chosen inflorescences, at the flowering season, from over 50% of the plants each plot. The following parameters were analysed: seed dry weight and moisture content, germination percentage, and seed speed of emergence (vigor). A coincidence between the point of maximum dry weight, germination percentage and vigor and lower moisture content was observed, although the climatic conditions had effects due to the different sowing periods. Maximum germination and vigor occurred, in an overall analysis at the 58th day after flowering for the three sowing periods. Also the greatest dry weight occurred at the 58th day, except for the period of December that had that value at the 65th day after flowering. The lowest moisture content of the seeds was detected at 58, 64 and 72 days after flowering for the first, second and third sowing periods, respectively.